Electric Drive and Automation of Sampling System for Chimney Fas Analyzer - V. I. Emeliantchikov; E. E. Loikuts; O. F. Opeiko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2024)
To organize reliable control over emissions from chimneys of energy facilities, automatic monitoring systems are needed. Equipment is known for monitoring emissions from small-diameter chimneys, but for large-diameter pipes (15 m or more) available in our Republic, there are no corresponding technical solutions.  The paper examines the problem of automating the sampling of flue gases based on an electric drive in large-diameter chimneys. To ensure the optimal trajectory of the sampler in the chimney section, it is necessary to use an asynchronous electric motor with a frequency converter and a position sensor. A functional diagram of the control system is proposed, which contains a programmable logic controller for generating the motion mode, as well as a method for calculating parameters and expressions for generating a task signal for continuous sampling mode. Since the range of speed control increases as the diameter of the chimney increases, depending on it, scalar or vector frequency control can be applied. An expression is proposed for calculating the optimal value of the parameter N of an incremental position and speed sensor (encoder), which contributes to a reasonable choice of sensor. The results of simulation modeling are presented, confirming the effectiveness of the proposed method for calculating the parameters of the sampler drive.